2022
DOI: 10.3389/fvets.2022.850771
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fluoride on Cytotoxicity Involved in Mitochondrial Dysfunction: A Review of Mechanism

Abstract: Fluoride is commonly found in the soil and water environment and may act as chronic poison. A large amount of fluoride deposition causes serious harm to the ecological environment and human health. Mitochondrial dysfunction is a shared feature of fluorosis, and numerous studies reported this phenomenon in different model systems. More and more evidence shows that the functions of mitochondria play an extremely influential role in the organs and tissues after fluorosis. Fluoride invades into cells and mainly da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 138 publications
0
7
0
Order By: Relevance
“…Fions in concentrations exceeding 100 ppm can be toxic for promoting the generation of reactive oxygen species, and possibly explain the cytotoxic results in MILD-Ti 3 C 2 T x . [84,85] In addition, cell staining and flow cytometry analysis were also carried out using live/dead and apoptosis assay kit in living cells after treating with 72-h-aged NaOH-Ti 3 C 2 T x and MILD-Ti 3 C 2 T x which the cell viability assays started to deviate significantly. The micrographs showed that most cells were viable in the NaOH-Ti 3 C 2 T x MXene treated group as the dead cells with red fluorescence were hardly observed (Figure 5e).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fions in concentrations exceeding 100 ppm can be toxic for promoting the generation of reactive oxygen species, and possibly explain the cytotoxic results in MILD-Ti 3 C 2 T x . [84,85] In addition, cell staining and flow cytometry analysis were also carried out using live/dead and apoptosis assay kit in living cells after treating with 72-h-aged NaOH-Ti 3 C 2 T x and MILD-Ti 3 C 2 T x which the cell viability assays started to deviate significantly. The micrographs showed that most cells were viable in the NaOH-Ti 3 C 2 T x MXene treated group as the dead cells with red fluorescence were hardly observed (Figure 5e).…”
Section: Resultsmentioning
confidence: 99%
“…F – ions in concentrations exceeding 100 ppm can be toxic for promoting the generation of reactive oxygen species, and possibly explain the cytotoxic results in MILD‐Ti 3 C 2 T x . [ 84,85 ]…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, rupture of the outer mitochondrial membrane leads to Cyt c release from the intermembrane space and subsequent inner mitochondrial membrane depolarization ( 56 ). At the same time, mitochondrial membrane potential(MMP) decrease, in turn, leads to Cyt c release ( 57 ). In the cytoplasm, apoptosomes formed with Cyt c, apoptotic protease-activating factor 1 (Apaf-1), and caspase-9 trigger caspase-3 activation, ultimately leading to apoptosis ( 10 , 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial complexes I, II, and III, play an important role in regulating mitochondrial function and ATP production and are the main checkpoints for electron entry into the mitochondrial electron transport chain [ 56 , 57 ], where the entry and exit of the ions inside and outside the membrane take place. NaF treatment at a low or high concentration for a short period increases the mitochondrial activity of the complex-I, as shown in our study ( Fig 4 , Table 1 ).…”
Section: Discussionmentioning
confidence: 99%